Modeling Languages and Condor: Metacomputing for Optimization - Munson, Todd; Ferris, Michael (My University, 1998)
A generic framework for utilizing the computational resources provided by a metacomputer to concurrently solve several optimization problems generated by a modeling language is postulated. A mechanism using the Condor resource manager and the AMPL and GAMS languages is developed and applied to a technique for solving a mixed integer programming formulation of the feature selection problem. Due to the method?s computational requirements, the ability to perform optimizations in parallel is necessary in order to obtain results within a reasonable amount of time. We provide details about our simple and easy to use tool and implementation so that other modelers with applications generating many independent mathematical programs can take advantage of it to significantly reduce duration.
Keywords: Condor; modeling languages